Role of CYP1A1 in the biological activity of methylated resveratrol analogue, 3, 4, 5, 4′-tetramethoxystilbene (DMU-212) in ovarian cancer A-2780 and non-cancerous HOSE cells. (5th February 2017) - Piotrowska-Kempisty, Hanna; Klupczyńska, Agnieszka; Trzybulska, Dorota; Kulcenty, Katarzyna; Sulej-Suchomska, Anna Maria; Kucińska, Małgorzata; Mikstacka, Renata; Wierzchowski, Marcin; Murias, Marek; Baer-Dubowska, Wanda; Kokot, Zenon; Jodynis-Liebert, Jadwiga
Graphical abstract: Highlights: CYP1A1 is the major enzyme of CYP1 family involved in the biotransformation of DMU-212. The cytotoxic effects of DMU-212 are related to the expression of CYP1A1 enzyme. The biological activity of DMU-212 is associated with its metabolic activation to DMU-214. Abstract: The role of CYP1A1 and CYP1B1 enzymes in the biotransformation and biological activity of the methylated resveratrol analogue, 3, 4, 5, 4′-tetramethoxystilbene (DMU-212) is still elusive. Our recently published data have shown that one of the metabolites of DMU-212, 3′-hydroxy-3, 4, 5, 4′-tetramethoxystilbene (DMU-214) exerts more potent cytotoxic effects in A-2780 ovarian cancer cell line, as compared to the parent compound. Hence, this study aims to elucidate whether the biological activity of DMU-212 is related to its biotransformation to DMU-214. Furthermore, we aimed to assess which enzymes of CYP1 family are involved in the biotransformation of DMU-212. The human ovarian cancer cell lines A-2780, A-2780CYP1A1(−) and non-cancerous human ovarian surface epithelial (HOSE) cells were employed in the present study. In contrary to other authors' suggestions we have found that CYP1A1 is the major enzyme of CYP1 family involved in the metabolic activation of DMU-212. Since the distinctly weaker anti-proliferative effects of DMU-212 against HOSE and A-2780CYP1A1(−) cells have been associated with the lack of the expression of CYP1A1, we suggest that the biological activity of the parent compound may be related to its metabolic activation to DMU-214 and the level of this enzyme.